İşaret dilinin tarihi serüveni ve Türk işaret dili - Erten, Hüsnü; Arıcı, Nursal (Afyon Kocatepe Üniversitesi)
İşaret dilleri, sağırların hem birbirleriyle hem de diğer kişilerle iletişim kurabildikleri doğal dillerdir. İşaret dilleri hakkında toplumda birçok yanlış kanı vardır. Bunlardan en yaygını tüm dünyada tek bir işaret dili kullanıldığı düşüncesidir. Bu durumun temel sebebi, işaret dillerinin yalnızca sağırlar, yakınları ve konuya ilgi duyan küçük bir kesim tarafından biliniyor olmasıdır. Bunun yanı sıra toplumda yeterli düzeyde farkındalık olmaması işaret dilleri hakkında yanlış kanıların oluşmasına neden olmuştur. Bu çalışmanın amacı, sağırların durumunun ve işaret dillerinin tarihsel süreç bağlamında ele alınmasıyla konu hakkında toplumda farkındalık oluşturmaktır. Ayrıca en eski işaret dillerinden biri olan Türk işaret diline özel olarak dikkat çekmek istenmiştir. Sağırlar tarih boyunca farklı toplumlarda birbirinden çok farklı muameleler görmüşlerdir. Temeli Antik Çağlara dayanan bir anlayışla, sağırların zekâ engelli olduğu ve eğitilemeyeceği düşüncesi, Avrupa’da Orta Çağ’ın sonlarına kadar devam etmiştir. Bu durum ancak Rönesans’tan sonra değişebilmiştir. Osmanlı’da ise sağırlar topluma iyi bir şekilde uyum sağlamışlardır. İşaret dilini kullanarak toplumla iletişim kurabilmişler, birçok farklı alanda çalışma imkânı bulmuşlardır. Osmanlı’da işaret dilinin 400-500 yıldan beri kullanıldığına dair ipuçları vardır. Türk İşaret Dili’nin Osmanlıda kullanılan işaret dilinin devamı olduğu düşünülmektedir. Çalışmada, işaret dillerinin ortaya çıkmasından günümüze kadar geçirdiği süreç, ilgili literatür bağlamında, tarih çağları takip edilerek incelenmiştir.

Sign languages are the natural languages in which the deaf individuals can communicate with each other and with other people. There are many misconceptions about sign languages in society. The most common of these is the idea that a single sign language is used all over the world. The main reason for this is that sign languages are only known by the deaf individuals, their relatives and a small group of people interested in the subject. In addition to this, the lack of sufficient awareness in the society has caused misconceptions about sign languages. The aim of this study is to raise awareness about the issue in society by considering the situation of deaf individuals and sign languages in the context of the historical process. Besides, special attention wanted to be paid to the Turkish sign language, one of the oldest sign languages. Deaf individuals have been treated very differently in different societies throughout history. With an understanding based on Ancient Times, the idea that deaf individuals are mentally impaired and cannot be educated continued in Europe until the end of the Middle Ages. This situation could only change after the Renaissance. On the other hand, deaf individuals have adapted well to the society in the Ottoman Empire. They were able to communicate with the society by using sign language, and they had the opportunity to work in many different fields. There are clues that sign language has been used in the Ottoman Empire for 400-500 years. It is thought that Turkish Sign Language is the continuation of the sign language used in the Ottoman Empire. In the study, the process of sign languages from their emergence to the present day has been examined in the context of the relevant literature by following the historical ages.
Historical headway of sign language and Turkish sign language
Keywords: İletişim; Sağırlar; İşaret Dili; İşaret Dili Tarihi; Türk İşaret Dili; Communication; Deaf People; Sign Language; History of Sign Language; Turkish Sign Language